2004
DOI: 10.1016/j.febslet.2004.07.084
|View full text |Cite
|
Sign up to set email alerts
|

Transport of somatostatin and substance P by human P‐glycoprotein

Abstract: P-glycoprotein is an efflux pump for a broad spectrum of hydrophobic agents. We found that bioactive peptides including somatostatin and substance P inhibit ATPdependent vincristine binding to P-glycoprotein-overexpressing K562/ADM membrane vesicles. Some of these bioactive peptides including somatostatin stimulate basal ATPase activity of P-glycoprotein; in contrast, other peptides including substance P inhibit it. The K562/ADM membrane vesicles showed an ATPdependent, osmotically sensitive uptake of somatost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…There was a 450-fold difference in the expression of the ABC transporter family gene MDR1 in 'highresistance' PC3R cells compared with the PC3wt cells. Uchiyama-Kokubu et al [20] previously investigated whether SST can interact with Pgp; they showed that they interact at a vincristine-binding locus and that SST is transported into plasma membrane vesicles prepared from K562/ADM cells, indicating that Pgp transports SST. Our data suggest that lanreotide could act as a Pgp blocker in 'high-resistance' PC3R cells.…”
Section: Discussionmentioning
confidence: 99%
“…There was a 450-fold difference in the expression of the ABC transporter family gene MDR1 in 'highresistance' PC3R cells compared with the PC3wt cells. Uchiyama-Kokubu et al [20] previously investigated whether SST can interact with Pgp; they showed that they interact at a vincristine-binding locus and that SST is transported into plasma membrane vesicles prepared from K562/ADM cells, indicating that Pgp transports SST. Our data suggest that lanreotide could act as a Pgp blocker in 'high-resistance' PC3R cells.…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that FGF2 was capable of entering the vesicles as evidenced by protection from the protease [37]. A similar method has been used to assess the transmembrane transport behavior of somatostatin [228]. …”
Section: Model Membrane Systems To Study the Nonclassical Protein mentioning
confidence: 99%